Hubungan Kunjungan Posyandu, ASI Eksklusif dan MP ASI dengan Kejadian Stunting di Wilayah Kerja UPTD Puskesmas Kereng Pangi: Relationship Between Posyandu Visits, Exclusive Breastfeeding and MP ASI with Stunting in the Working Area of the UPTD Kereng Pangi Health Center - Welly, Yun; Meyasa, Lola; Resmaniasih, Ketut (Jurnal Surya Medika (JSM), 2023)
Cases of nutritional problems or disorders in toddlers are currently increasing in developing countries, including Indonesia. The Height-for-Age Index (TB/U) provides an indication of chronic nutritional problems as a result of long-lasting conditions, for example due to poverty, unhealthy lifestyle, and insufficient food intake for a long time resulting in stunting in children. Currently, the Province of Central Kalimantan has the 14th highest prevalence of stunting in Indonesia and the prevalence of stunting in Katingan Regency is ranked 6th highest in Central Kalimantan. Purpose This study was to determine the relationship between Posyandu visits, exclusive breastfeeding and MP-ASI with stunting in children under five in the UPTD Work Area of ​​the Kereng Pangi Health Center in 2023. Methods the research design used in this study was an analytic survey with a cross sectional approach. The study population was all mothers and children aged 24-59 months in the working area of ​​the UPTD Puskesmas Kereng Pangi for the period February-May 2023. The sampling technique was Stratified Random Sampling and the sample was taken by Simple Random Sampling. The sample size in this study was 133 toddlers. Primary data types using a questionnaire. Univariate data analysis using presentation and bivariate analysis. The statistical test used was the Chi-Square test with an alpha of 0.05. Results based on the results of statistical tests, it was found that there was a relationship between posyandu visits and stunting (p-value 0.002), exclusive breastfeeding with stunting (p-value 0.004) and MP ASI with stunting (p-value 0.001) in the working area of ​​the UPTD Puskesmas Kereng Pangi. Conclusion there is a relationship between Posyandu visits, exclusive breastfeeding and MP ASI with stunting.